Semantically holistic and personalized views across heterogeneous information sources - HAMPSON, CORMAC; CONLAN, OWEN; HAMPSON, CORMAC (My University, 2007)
A consolidated view of the content within different data repositories would facilitate useful operations such as advanced informational discovery. This paper proposes a methodology and an architecture that uses semantic annotations to enable such holistic views across domain specific information sources. The potential for the personalization of this annotated information is described, and the future work necessary to implement the system is elaborated on.
Proceedings of the 2nd International Workshop on Semantic Media Adaptation and Personalization
2nd International Workshop on Semantic Media Adaptation and Personalization
PUBLISHED
London
Keywords: Computer Science